Construction expression and immunogenicity of a novel trivalent outer membrane protein (OmpU‐A‐II) from three bacterial pathogens in Japanese eels (Anguilla japonica). Issue 5 (13th April 2020) - Zhao, Jinping; Wu, Liqun; Zhai, Shaowei; Lin, Peng; Guo, Songlin
Abstract: Vibrio vulnificus, Edwardsiella anguillarum and Aeromonas hydrophila are three common bacterial pathogens in cultivated eels. To protect farming eels from infection by these pathogens, a trivalent outer membrane protein (OMP) containing partial sequences of OmpU from V. vulnificus, OmpA from E. anguillarum and OmpII from A. hydrophila was expressed and purified; then, the OMP was used as a vaccine to immunize Japanese eels ( Anguilla japonica ). Whole‐blood cell proliferation, antibody titres and complement and lysozyme activities were detected at different days post‐immunization (dpi), and the relative per cent survival (RPS) was determined after eels were infected with V. vulnificus, E. anguillarum or A. hydrophila at 28 dpi. The results showed that the OMP significantly stimulates the antibody titres. At 14 days after the challenge (i.e. at 28 dpi), the RPS of OMP against V. vulnificus, E. anguillarum and A. hydrophila was 20%, 70% and 11.1%, respectively. The construction, expression and immunogenicity of a trivalent Omp were reported for the first time, and this study will provide a valuable reference for the development of fish multiplex vaccines.